Annual Plan 1999-2000 Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1997)
Annual plan 1998-99 started with an adhoc allocation of Rs. 1500 crores. The allocation was decided by Planning Commission at Rs. 1900 crores in August, 1998. The plan included an ARM component of Rs. 262.14 crores to be made up by joint efforts of the Central and State Government and project linked loan assistance of Rs 181.18 crores. The project linked loan target was 50% more than the similar component in the plan of the proceeding year and 9.54% of 1998-99 plan.
Government of Jammu and Kashmir, Planning and Development Department